Oral Health by Using Probiotic Products - Mahmoudi, Razzagh (Biochemistry, 2019)
One of the most prevalent and important health problems in the world is periodontal and plaque-related diseases for which antibiotic drugs with their associated side effects are used as treatment. With increasing resistance to antibiotics and a desire from the general public for "natural" therapies, there is a need to minimize antibiotic use and develop new treatments for oral diseases without antimicrobial agents. Probiotics are viable microorganisms that provide a health benefit to the host when administered in adequate amounts; studies show that probiotics have the potential to modify the oral microbiota and decrease the colony-forming unit counts of the oral pathogens being investigated to prevent or treat oral diseases, such as dental caries and the periodontal diseases. In addition, the identification of specific strains with probiotic activity is required for any oral infectious disease to determine the exact dose, the time of treatment, and the ideal vehicle.